Software visual specification for requirement specification validation - Fauziah, Zainuddin; Ruzaini, Abdullah Arshah; Rozlina, Mohamed (Association for Computing Machinery (ACM), 2018)
Informal specifications are commonly adopted for requirements engineering (RE), especially for customer-oriented system development projects, but their validity with respect to the user's requirements is usually difficult to perform. The common reason for the difficulty is that the specifications are often misinterpreted by the stakeholders due to the ambiguity of the natural language. This paper describes a procedure in transforming the informal specification into specification visual specification. The transformation procedure is developed based on the extended version of software visualization taxonomy. The underlying software visualization specification principle is called Requirement Engineering (specification) for Human Factor validation (REsHFv). The framework is devoted to human factor involvement in validating the informal specification using software visualization as interaction medium.